Blood Lead Level and Handgrip Strength in Preadolescent Polish Schoolchildren - Natalia Nowak-Szczepanska; Aleksandra Gomula; Anna Sebastjan; Zofia Ignasiak; Robert M. Malina; Sławomir Kozieł (Toxics, 2022)
Environmental pollutions, particularly toxic elements such as lead, are among the most significant factors affecting the growth and functional development of children. The aim of this study was to evaluate the effect of blood lead levels on handgrip strength (HGS) in urban children resident in the Copper Basin of Lower Silesia, Poland, controlling for the effects of chronological age, body size and socioeconomic status. The study included 165 boys (9–11 years of age) and 79 girls (9–10 years of age) from Polkowice town. Anthropometric measurements involved height, body mass and grip strength of the left and right hands. Maternal education was a proxy for socioeconomic status. Based on the median value of blood lead level (3.10 µg/dL), the two groups-below and above/equal median value-were defined. Analysis of covariance revealed that age (all p < 0.001), sex (at least p < 0.01), BMI (all p < 0.001), and blood lead level (at least p < 0.05) had a significant effect on the three indicators of HGS (right hand, left hand, average), while the level of maternal education did not significantly affect HGS (p > 0.05). The results of this study indicate a potentially negative effect of elevated blood lead level on grip strength in preadolescent children, irrespective of sex.